Adopting Learner-Centred Pedagogy to Develop Business Studies Learners' Problem-Solving and Creative Thinking Skills in Selected Schools in South Africa - Gcabashe, Nduduzo Brian (Research in Social Sciences and Technology- OpenED Network, 2024)
The need for problem-solving and creative thinking skills to be taught well in business studies classrooms can never be overemphasised due to the complexity of the problems and challenges faced by businesses in the 21st-century business environment. Teachers are, therefore, required to adopt pedagogies that would enable learners to acquire problem-solving and creative thinking skills to operate effectively in the new business environment. This study investigates business studies teachers' adoption of learner-centred pedagogy to nurture learners' problem-solving and creative thinking skills. This qualitative study is positioned within the interpretive paradigm. An exploratory case study was employed as a research design. Progressive Learning Theory was adopted as the lens of the study. Semi-structured interviews and classroom observations were used to collect data from six business studies teachers who were sampled purposefully from six secondary schools in KwaZulu-Natal province, South Africa. The raw data was analysed thematically. It was found that most teachers managed to adopt learner-centred pedagogy and learning activities that promoted the acquisition of problem-solving and creative thinking skills. The study concluded that business studies teachers are now embracing learner-centred pedagogy in their classrooms, and they understand the importance of teaching learners to equip them with skills that are demanded by the 21st-century business environment. Despite these findings, it is still recommended that workshops and short learning courses be offered to teachers to equip them with pedagogical skills that would help them to engrain and sustain learner-centred pedagogy in their instructional practices.